Gestational diabetes mellitus and polycystic ovary syndrome, a position statement from EGOI-PCOS - Paola Quaresima; Samuel H. Myers; Basilio Pintaudi; Basilio Pintaudi; Rosario D’Anna; Rosario D’Anna; Michele Morelli; Vittorio Unfer; Vittorio Unfer (Frontiers in Endocrinology)
Gestational diabetes mellitus is a worldwide health issue in pregnancy, posing a threat to both mother and child. One of the major risk factors for the development of gestational diabetes mellitus is polycystic ovary syndrome, primarily due to the biochemical hyperandrogenism and metabolic issues, commonly observed in these patients. In recent years, the Expert Group on Inositol in Basic and Clinical Research and on PCOS (EGOI-PCOS) has sought to better understand the pathogenesis behind polycystic ovary syndrome, in order to accurately diagnose and treat patients according to their individual needs. Through the scope of polycystic ovary syndrome, this position paper examines the characteristics of both conditions, and underlying biological mechanisms, before moving on to common treatment strategies to avoid or treat gestational diabetes mellitus in women with polycystic ovary syndrome.